A Decade of Global Navigation Satellite System/Acoustic Measurements of Back-Arc Spreading in the Southwestern Okinawa Trough - Chen, Horng-Yue; Ikuta, Ryoya; Hsu, Ya-Ju; Tsujii, Toshiaki; Ando, Masataka; Tu, Yoko; Kohmi, Takeru; Takemoto, Kiyomichi; Mizuno, Koto; Tung, Hsin; Ku, Chin-Shang; Lin, Cheng-Horng (Frontiers in Earth Science, 2021)
The sustained seafloor geodetic measurement is crucial, even yet sparse in time and space, to constrain the undersea crustal deformation near the plate boundaries. We present an integrated analysis of a decade of GNSS/Acoustic data collected at a site 60 km to the east of the northeast coast of Taiwan near the opening axis of the Okinawa trough back-arc basin. As a result, we obtained the horizontal and vertical positioning time series of the benchmark with eighteen measurements from 2009 to 2019. The positioning time series of the benchmark shows a southeastward movement at a rate of 43±5 mm/yr since 2012 with respect to the Yangtze plate. The horizontal motion can be explained by the clockwise block rotation of the Yonaguni block united with the northern part of the Central Range. In addition, the vertical displacement of the transponder array shows the rapid subsidence of 22±9 mm/yr from 2012 to 2019. The fast subsidence rate and the negative free-air gravity anomaly in this region indicate that the crustal thinning is compensated mainly by the surface deformation instead of the upward migration of the Moho. Considering the offset in 2012 due to the change of transponder array, the horizontal positioning time series of our site is best explained by two linear lines with a slope change in July 2013. The timing of the velocity change roughly coincides with the change of the periphery seismicity rate and the dike intrusion 150 km away from the site. The results show the potential of the seafloor geodesy site in accessing the temporal variation in the deformation rate near the spreading center of the Okinawa Trough, which is not accessible by on-land GNSS stations.